Tafsīr filantropīyat al-Qur’ān al-Karīm fī Indonesia: Musāhamat Tafsīr Sūrat al-Mā‘ūn li Kiai al-Ḥāj ‘Abd al-Ḥalīm (1887-1962) - Rohmana, Jajang A. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
This article discusses the Quranic exegesis concerning social care that is used as a base-praxis for philanthropy and social gatherings in the colonial period. The object of this study is Tafsier Soerat Al-Ma’oen (1930) written by K.H. Abdulchalim. This Sundanese-language work is actually developed as the result of Abdulchalim’s reading on the Quranic exegesis of Juz ‘Amma was written by Muhammad Abduh. Abdulchalim tried to interpret this surah and made it as the basis of the his philanthropic activities through the establishment of social institutions rather than carrying out casitas activities which he considered momentary and consumtive. His social activities were based on the teachings of philanthropy contained in the al-Mā‘ūn surah, such as philanthropic orientation from individual to collective, attachment between praying and the fulfilment of weak people’ right, criticism of the Muslim backwardness, and colonial occupation over his homeland. This study confirms that the Abdulchalim’s interpretation cannot be separated from the social situation as a nation that was being colonized faced with Dutch colonial policy and competition with Chinese traders. His exegesis becomes another example from the influence of Islamic renewal thrived in Cairo toward Southeast Asian Muslim activists, especially in the pre-independence period.